1991
DOI: 10.1111/j.1432-1033.1991.tb16073.x
|View full text |Cite
|
Sign up to set email alerts
|

Primary structure of bovine lactoperoxidase, a fourth member of a mammalian heme peroxidase family

Abstract: Much is known about bovine lactoperoxidase but no data are available on its primary structure. In this work its main active fraction was isolated from cow's milk and sequenced using a conventional strategy. A clear similarity was found with human myeloperoxidase, eosinophil peroxidase and thyroperoxidase, the sequences of which were recently elucidated from those of their cDNAs and/or genes. The single peptide chain of bovine lactoperoxidase contains 61 2 amino acid residues, including 15 half-cystines and 4 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
51
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(57 citation statements)
references
References 32 publications
5
51
0
Order By: Relevance
“…This agrees with NMR data for MPO and LPO where spectral similarities between the two mammalian peroxidases were observed (22). It is also consistent with reported sequence similarities between the two proteins (8,9). The two substituents should be sufficient to induce the observed red shifting of the MCD data and to prevent ready removal of the LPO heme without causing the complete spectral changes observed for MPO.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This agrees with NMR data for MPO and LPO where spectral similarities between the two mammalian peroxidases were observed (22). It is also consistent with reported sequence similarities between the two proteins (8,9). The two substituents should be sufficient to induce the observed red shifting of the MCD data and to prevent ready removal of the LPO heme without causing the complete spectral changes observed for MPO.…”
Section: Discussionsupporting
confidence: 80%
“…Thus, we suggest that the LPO heme (called here heme l) is distinct from either heme b or heme m, although it has similar peripheral substituents to each. Given the high degree of spectral and protein sequence agreement between mammalian peroxidases (8,9,19), we suggest that the heme l of LPO, or a very closely related heme, is likely to also be the heme of TPO, SPO, eosinophil peroxidase, and other mammalian peroxidases.…”
mentioning
confidence: 99%
“…Later studies showed that this sulfonium ion linkage involved the vinyl group of pyrrole ring A (13,16). Met 243 is replaced by a threonine in human EPO (10), whereas in bovine LPO a glutamine is found at this position (17), and, as recently shown by Ueda et al (11), in human LPO a histidine is present. It should be mentioned that the genetic codes of Gln and His only differ by one base for both residues.…”
mentioning
confidence: 89%
“…Breastfed sucklings, for example, almost exclusively exhibit Bifidobacterium bifidum in their intestine [2]. Milk proteins which are supposed to be responsible for this modulation are for example lysozyme [3,4], lactoperoxidase [5][6][7], lactoferrin [7][8][9] and antibodies [10]. However, in vivo the ingestion of lactoferrin has only a marginal influence on the intestinal microflora [1 1].…”
Section: Introductionmentioning
confidence: 99%